Satisfaction Rate from the Communication Skills of Family Physicians in Rural Health Centers at Mazandaran University of Medical Sciences - Rezaali Bagheri; Seyed Ahmad Mohammadikia; Mehraneh Kazemian; Batuol Kazemi; Meysam Rezapour (Babol University of Medical Sciences, 2014)
BACKGROUND AND OBJECTIVE: Since that one of the basic points in the competences of physicians, is the communication skill to carry out their professional duties properly, several studies suggest that manyphysicians can not communicate to their patients, effectively.How to communicate and interact with patients plays an effective role in the patient satisfaction, treatment results, medical costs, the quality of clinical services, and even in the complaints from the doctors. This study was performed with the aim of determining the satisfaction rate about the communication skills of family physicians in rural health centers at Mazandaran University of Medical Sciences in the viewpoints of the individuals referring them in the year 2012. METHODS: This descriptive- cross sectional study, was performed on 315 patients referring to family physicians of rural health centers in Mazandaran province in the year2012. Data collecting was performed by using Farmahini questionnaire (2006). Questionnaire includes 24 questions in six areas: how to deal with the patient initially, how to take a medical interview, how to contact with the patient, in physical examination, how to educate, how to follow up the patient and the time duration for follow the patients problems by the doctor. Data analysis was performed by spss software with significant level of 0.95. FINDINGS: The study results showed that 153 individuals (48.6%) of patients, were unsatisfied about the service providing of family physicians. 53 persons (16.9%) had moderate satisfaction and only 109 persons (37.8%) were completely satisfied. Older persons had more satisfaction rate in comparison to other age groups. In higher educational levels, the rate of satisfaction was decreased. CONCLUSION: According to findings, the most basic expectation of people from medical team is effective and humanistic communication, in this manner, diagnostic and therapeutic patterns will be effective and completed. For better attitude of the patients about doctors, notification to the emotional and mental aspects of the patients should be improved in the physicians.